Моделювання системних факторів забезпечення фінансової безпеки суб’єктів агропродовольчого ринку на регіональному рівні - Козак, В. М.; Kozak, V. M. (Запоріжжя : ТДАТУ, 2024)
UA: В статті розглянуто процес моделювання системних факторів фінансової безпеки суб’єктів агропродовольчого ринку на регіональному рівні. Використано на засадах системного підходу математичний інструментарій до оцінювання фінансової безпеки суб’єктів агропродовольчого ринку в часовому просторі. Встановлено кількісні та якісні параметри загроз ендогенного та екзогенного характеру, що ідентифікують пороговий інтервал стійкого фінансового стану суб’єктів агропродовольчого ринку на регіональному рівні. Виокремлено системні фактори стимулюючого та дестимулюючого характеру для оцінки фінансової безпеки суб’єктів агропродовольчого ринку та запропоновано множину індикаторів для аналізу складових фінансової безпеки, що забезпечують процес нейтралізації реальних та потенційних загроз забезпечення стабільного рівня фінансової безпеки суб’єктів агропродовольчого ринку. Обґрунтовано доцільність здійснення нормалізації індикаторів, врахування їх порогові значення, вагові коефіцієнти та структуру капіталу при розрахунку інтегрального рівня фінансової безпеки. Доведено, що впровадження системних факторів за загальним рівнем фінансової безпеки дозволяє підвищити фінансову стійкості функціонування суб’єктів агропродовольчого ринку. EN: Abstract. The article examines the process of modeling systemic factors of financial security of agro-food market entities at the regional level. A mathematical toolkit for assessing the financial security of agro-food market subjects in time is used based on the principles of a systematic approach. Quantitative and qualitative parameters of threats of an endogenous and exogenous nature have been established, which identify the threshold interval of a stable financial condition of subjects of the agro-food market at the regional level. Systemic factors of a stimulating and disincentive nature for assessing the financial security of subjects of the agro-food market are singled out and a set of indicators are proposed for the analysis of the components of financial security, which ensure the process of neutralizing real and potential threats to ensure a stable level of financial security of subjects of the agro-food market. The expediency of the rationing of indicators, which take into account their threshold values, weighting factors and capital structure for calculating the integral level of financial security, is substantiated. It has been proven that the introduction of systemic factors at the general level of financial security allows increasing the financial stability of the functioning of the subjects of the agro-food market. Destabilization of the financial condition of enterprises worsens the conditions of their operation and leads to insolvency, a decrease in investment attractiveness and creditworthiness, and as a result – makes it impossible to attract financial resources from external sources. Improving the concentration of capital in general has a positive effect on the financial condition and efficiency of the work of the subjects of the agro-food market. It has been proven that the forecast value of the integral indicator is greater than in previous periods, which indicates a tendency towards an increase in the level of financial security of subjects of the agro-food market of the Kyiv region. This will be facilitated by the accelerated growth of accounts payable, equity and profit. The tendency to decrease the value of fixed assets and the amount of income will have a negative impact on the level of financial security.
Modeling of system factors of security financial security of agricultural market subjects at the regional level
Keywords: фінансова безпека; ефективність; загрози; суб’єкти агропродовольчого ринку; фінансовий стан; фінансова рівновага; financial security; efficiency; threats; subjects of the agro-food market; financial condition; financial balance